Using temozolomide in newly diagnosed glioblastoma multiforme – a single-centre experience - Ziółkowska, Ewa; Wiśniewski, Tomasz; Zarzycka, Małgorzata; Windorbska, Wiesława; Lebioda, Andrzej; Makarewicz, Roman (Contemporary Oncology/Współczesna Onkologia, 2010)
Background : Temozolomide in association with radiotherapy and after irradiation is a treatment recommended in countries of the EU and USA as the first choice in glioblastoma multiforme. For several years this drug has been used in Poland as a non-standard chemotherapy. The aim of this study was to assess the efficacy of treatment and the toxicity profile of this kind of treatment and compare our results with other researchers. Material and methods: 30 patients with glioblastoma multiforme diagnosed histopathologically were involved in this investigation. Everyone received radiotherapy (60 Gy in 30 fractions) and temozolomide (75 mg/m 2 ) during the irradiation, and then as adjuvant chemotherapy (150 mg/m 2 ) in 6 monthly cycles, except for patients with recognized progression of the disease during the therapy. The OS, PFS and possible complications of applied therapy were evaluated. Results: During the median follow-up of 10 months (range 2-43) progression of the disease was observed in 20 patients (66%), of whom 19 patients died. Medians of the OS and the PFS were 14.6 months (95% CI: 12.4-16.8) and 7.8 months (95% CI: 5.94-9.66) respectively. Tolerance of the treatment was good with thrombocytopenia as the most often observed complication (20%). Severe complications were observed in 5 patients (17%). Conclusions: Temozolomide is a new, well tolerated and active drug used in the treatment of glioblastoma multiforme, and the results of our analysis are comparable to the results of the multicentric EORTC/NCIC investigation.